Respuesta :

By definition we have that the average rate of change of the function is:

 [tex]AVR = \frac{f(x2) - f(x1)}{x2 - x1} [/tex]

 Evaluating the function for the complete interval we have that the AVR is given by:

 [tex]AVR = \frac{115 - (-5)}{10 - (-2)} [/tex]

 Rewriting we have:

 [tex]AVR = \frac{115+5}{10+2} [/tex]

 Simplifying the expression we have:

 [tex]AVR = \frac{120}{12} [/tex]

 [tex]AVR = 10 [/tex]

 Answer:

 the average rate of change of the function defined by the table is:

 [tex]AVR = 10 [/tex]

Answer:

Average rate of change is 10 .

Step-by-step explanation:

Y = -5 , 35 , 75 , 115

X = -2 , 2 , 6 , 10

         y2 - y1

m =   ---------------  

          x2 - x1

           -5 - 35          -40

m =   ---------------  =  ----- -  = 10

            -2 - 2            -4

          75 - 115         -40

m =   ---------------  =  ----- -  = 10

            6 - 10            -4